Rethinking Maqāṣid al-Sharīʿa in Marital Relations: A Systems Approach to Female Migrant Worker Families - Ummu Aemanah; Idzam Fautanu; Usep Saepullah; Ending Solehuddin; Muhammad Yogi Sandra (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2026)
Classical discussions of marital relations in Islamic law generally assume physical co-residence and a stable domestic structure in which rights and obligations between husband and wife are clearly defined. This assumption becomes increasingly problematic in the context of female migrant worker families, where geographical separation and economic restructuring transform conventional marital roles. This article examines the theoretical tension between normative interpretations of maqāṣid al-sharīʿa and the lived realities of Female Migrant Worker Families. Using the maqāṣid-based systems approach developed by Jasser Auda, this study employs a qualitative conceptual-normative method through descriptive-interpretative analysis of Qur’anic verses (Q. 2:228; 4:19; 4:34; 30:21), relevant hadiths, and classical as well as contemporary Islamic legal scholarship. The analysis explores how justice, authority, and marital responsibility are renegotiated under conditions of long-distance marriage and female labor migration. The findings demonstrate that classical role-based interpretations of marital obligations are insufficient to address the complex realities of female migrant worker families. A systems-oriented maqāṣid framework instead conceptualizes marital relations as dynamic, relational, and purpose-driven, prioritizing justice (ʿadl), mutual care, and human dignity over fixed hierarchical roles. This study contributes conceptually by repositioning maqāṣid al-sharīʿa from a normative doctrine into an adaptive ethical framework capable of responding to contemporary socio-economic transformations in Muslim family life